(3GdSjQ hGdSdhc Edi edc Gdedhcs - (3bGSe Hf UdGM GdOjf GdNGfj GdMdHj,J (B1109 (3g` s ((3Ydi Wg GdYHSi GdOGQZQGhi s)
(3ChdgG (B:s
(3gPG cJGH GdSjQ hGdSdhc Edi edc Gdedhc JCdja GdTjN GdEeGe HSe Gddg GdQMef GdQMje GdMeO ddg GdPi CgHW HMceJg CSQGQ PGJg s
(3BNQgG (B:s
(3hdG JbOQ CjgG GdCN Ydi QOgG EdG HGdJeSc HGdTQjYI hUMHI GdYdeGA GdYGedjf hUdi Gddg Ydi CTQa GdCfHjGA hGdeQSdjf hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B104 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B833s
Keywords: (3GdJUha hGdBOGH GdTQYjIs